Biology, Ecology, and Management of Prevalent Thrips Species (Thysanoptera: Thripidae) Impacting Blueberry Production in the Southeastern United States - Rosan Adhikari; David G. Riley; Rajagopalbabu Srinivasan; Mark Abney; Cera Jones; Ashfaq A. Sial (Insects)
Blueberry is a high-value fruit crop in the United States, with Georgia and Florida serving as important early-season production regions. In these areas, several thrips species (Thysanoptera: Thripidae), including Frankliniella tritici (Fitch), Frankliniella bispinosa (Morgan), and Scirtothrips dorsalis (Hood), have emerged as economically significant pests. While F. tritici and F. bispinosa primarily damage floral tissues, S. dorsalis targets young foliage. Their rapid reproduction, high mobility, and broad host range contribute to rapid population buildup and complicate the management programs. Species identification is often difficult due to overlapping morphological features and requires the use of molecular diagnostic tools for accurate identification. Although action thresholds, such as 2–6 F. tritici per flower cluster, are used to guide management decisions, robust economic thresholds based on yield loss remain undeveloped. Integrated pest management (IPM) practices include regular monitoring, cultural control (e.g., pruning, reflective mulch), biological control using Orius insidiosus (Say) and predatory mites, and chemical control. Reduced-risk insecticides like spinetoram and spinosad offer effective suppression while minimizing harm to pollinators and beneficial insects. However, the brief flowering period limits the establishment of biological control agents. Developing species-specific economic thresholds and phenology-based IPM strategies is critical for effective and sustainable thrips management in blueberry cropping systems.